Determinants Foreign Direct Investment (FDI) Inflow in ASEAN-8 - Hugo Leonardo Prasetyo Khafidzin (MediaTrend, 2021)
Foreign Direct Investment (FDI) is the foreign investment which has more advantages than portfolio investment, because there are transfer of technology and transfer of knowledge. The purpose of this research is to analyze the effect of exchange rate, human capital, and economic growth on FDI inflows in ASEAN-8 period 2010-2019. By using panel data regression (FEM), the results showed that economic growth, human capital, and the exchange rate has a significant effect on FDI flows in ASEAN-8 countries.